2002
DOI: 10.2337/diabetes.51.12.3435
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Increase Human Islet Cell Mass While Preserving β-Cell Function

Abstract: Human islet expansion in monolayer culture leads to loss of function and senescence. By maintaining the 3-D configuration of islets in fibrin gels, it is feasible to expand ␤-cells in response to hepatocyte growth factor (HGF) while preserving physiologic glucose responsiveness both in vitro and in vivo after transplantation into nude mice. Islets were cultured free floating with or without growth factors and nicotinamide and in fibrin gels with the same conditions. Proliferation was observed only in islets cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(149 citation statements)
references
References 30 publications
5
142
1
1
Order By: Relevance
“…However, there are limitations because of the nature of the biomaterials employed. While several of the more effective substrates support longterm glucose responsiveness in vitro, the use of these materials poses technical problems for the retrieval of cells for subsequent transplantation [16], and if co-transplanted, the poor rate of vascularisation within such artificial scaffolds would inevitably impede the flow of nutrients and metabolites within the islet graft, leading to central necrosis and cell death [17]. Thus, whilst effectual in vitro, the use of artificial matrices is at present incompatible with clinical islet transplantation and must await further development.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are limitations because of the nature of the biomaterials employed. While several of the more effective substrates support longterm glucose responsiveness in vitro, the use of these materials poses technical problems for the retrieval of cells for subsequent transplantation [16], and if co-transplanted, the poor rate of vascularisation within such artificial scaffolds would inevitably impede the flow of nutrients and metabolites within the islet graft, leading to central necrosis and cell death [17]. Thus, whilst effectual in vitro, the use of artificial matrices is at present incompatible with clinical islet transplantation and must await further development.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports indicate that culturing human adult islets in fibrin for 1 week followed by transplantation of the cells resulted in improved graft size, reduced ductal structures, and significantly increased c-peptide levels compared with animals that received free-floating cultured islets. 25 It was postulated that the angiogenicpromoting effects of fibrin are what led to such results. These effects have also been observed when a fibrin hydrogelislet composite was subcutaneously transplanted in mice.…”
Section: Discussionmentioning
confidence: 99%
“…28 Indeed, transplantation of human fetal pancreatic cells into athymic diabetic mice leads to normo-glycemia 29 and the use of fibrin may assist in graft survival and function. 25,30 Therefore, the objective of this study is to analyze whether fibrin can promote human fetal pancreas differentiation and proliferation in vitro and in vivo as well as the potential mechanisms involved. We hypothesize that fibrin will promote differentiation of human fetal pancreatic progenitor cells into insulin producing cells through integrin αVβ3 receptor upregulation, and stimulate angiogenesis and cell proliferation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transfer of the gene for these proteins increased islet numbers, size and insulin content at least partly through decreased apoptosis. [56][57][58] This approach aims at enhancing islet yield for transplantation and could be an adjunctive measure for optimizing cadaveric islet transplantation. Clinical trials on this approach have not been reported.…”
Section: Ex Vivo Conversion Of Cells Into Functional B-cellsmentioning
confidence: 99%